ANSWER
1. (g o f)(5) = 4
2. (f o g)(3) = 2
3. g(f(4)) = 2
4. f(g(2)) = 0
Step-by-step explanation
1) (g o f)(5)
It is important to note that:
(g o f)(5) = g ( f(5) )
And so, we will find the value of f(5), then use that to find g (f(5))
f(5) is the value of f(x) when x is 5.
=> f(5) = 3
=> g(f(5)) = g(3)
g(3) is the value of g(x) when x is 3.
=> g(3) = 4
Therefore, g(f(5)) = 4
2) (f o g)(3)
That is f(g(3))
g(3) is 4.
=> (f o g)(3) = f(4)
f(4) = 2
Therefore, (f o g)(3) = 2
3) g(f(4))
f(4) = 2
=> g(2) = 2
Therefore, g(f(4)) = 2
4) f(g(2))
g(2) = 2
=> f(2) = 0
Therefore, f(g(2)) = 0